Dehydration Impairs Cognitive Performance: A Meta-analysis - Wittbrodt, Matthew T; Millard-Stafford, Melinda (Medicine and science in sports and exercise, 2018)
Dehydration (DEH) is believed to impair cognitive performance but which domains are affected and at what magnitude of body mass loss (BML) remains unclear. To conduct systematic literature review and meta-analysis to determine the effect size (ES) of DEH on cognitive performance and influence of experimental design factors (e.g., DEH > 2% BML). Thirty-three studies were identified, providing 280 ES estimates from 413 subjects with DEH ranging from 1% to 6% BML. Outcome variables (accuracy, reaction time), cognitive domains, and methods to induce DEH varied. Effect sizes were calculated using standardized mean differences and multivariate meta-analysis. Impairment of cognitive performance (all domains/outcomes) with DEH was small but significant (ES = -0.21; 95% confidence interval [CI]: -0.31 to -0.11; P < 0.0001) with significant heterogeneity (Q(279) = 696.0, P < 0.0001; I = 37.6%). Tasks of executive function (ES = -0.24; 95% CI: -0.37 to -0.12), attention (ES = -0.52; 95% CI: -0.66 to -0.37), and motor coordination (ES = -0.40 to 95% CI: -0.63 to -0.17) were significantly impaired (P ≤ 0.01) after DEH, and attention/motor coordination was different (P < 0.001) from reaction time specific tasks (ES = -0.10; 95% CI: -0.23 to 0.02). Body mass loss was associated with the ES for cognitive impairment (P = 0.04); consequently, impairment was greater (P = 0.04) for studies reporting >2% BML (ES = -0.28; 95% CI: -0.41 to -0.16) compared with ≤2%; (ES = -0.14; 95% CI: -0.27 to 0.00). Despite variability among studies, DEH impairs cognitive performance, particularly for tasks involving attention, executive function, and motor coordination when water deficits exceed 2% BML.